2001
DOI: 10.1152/physrev.2001.81.3.971
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Physiology of Kainate Receptors

Abstract: A decade ago, our understanding of the molecular properties of kainate receptors and their involvement in synaptic physiology was essentially null. A plethora of recent studies has altered this situation profoundly such that kainate receptors are now regarded as key players in the modulation of transmitter release, as important mediators of the postsynaptic actions of glutamate, and as possible targets for the development of antiepileptic and analgesic drugs. In this review, we summarize our current knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
263
0
7

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(281 citation statements)
references
References 193 publications
7
263
0
7
Order By: Relevance
“…Several studies have recognized age-related changes in the density and function of the different ionotropic glutamate receptors (Gonzales et al, 1991;Pittaluga et al, 1993;Nicoletti et al, 1995;Magnusson, 1998;Mitchell and Anderson, 1998;Wenk and Barnes, 2000). Although still somewhat controversial, many studies have shown that the expression of AMPA-, KA-and NMDA-sensitive receptors as well as the GABA A receptor is either constant or variably diminished in many different brain regions including the hippocampus during aging (Gonzales et al, 1991;Pittaluga et al, 1993;Le Jeune et al, 1996;Nicolle et al, 1996;EcklesSmith et al, 2000;Kuehl-Kovarik et al, 2000;Magnusson, 2000;Sonntag et al, 2000;Wenk and Barnes, 2000;Adams et al, 2001;Clayton and Browning, 2001;Clayton et al, 2002;Lerma et al, 2001). Differences in a variety of other factors, including voltage-gated calcium channels (Vigues et al, 1999;Kelly et al, 2003), androgen levels (Mejias-Aponte et al, 2002;Ramsden et al, 2003;Ciriza et al, 2004), and GABA receptor function (MacGregor et al, 1997;Ma et al, 2001) which have been shown to modulate kainate-induced seizure activity in young animals, may modulate susceptibility in aged animals as well.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recognized age-related changes in the density and function of the different ionotropic glutamate receptors (Gonzales et al, 1991;Pittaluga et al, 1993;Nicoletti et al, 1995;Magnusson, 1998;Mitchell and Anderson, 1998;Wenk and Barnes, 2000). Although still somewhat controversial, many studies have shown that the expression of AMPA-, KA-and NMDA-sensitive receptors as well as the GABA A receptor is either constant or variably diminished in many different brain regions including the hippocampus during aging (Gonzales et al, 1991;Pittaluga et al, 1993;Le Jeune et al, 1996;Nicolle et al, 1996;EcklesSmith et al, 2000;Kuehl-Kovarik et al, 2000;Magnusson, 2000;Sonntag et al, 2000;Wenk and Barnes, 2000;Adams et al, 2001;Clayton and Browning, 2001;Clayton et al, 2002;Lerma et al, 2001). Differences in a variety of other factors, including voltage-gated calcium channels (Vigues et al, 1999;Kelly et al, 2003), androgen levels (Mejias-Aponte et al, 2002;Ramsden et al, 2003;Ciriza et al, 2004), and GABA receptor function (MacGregor et al, 1997;Ma et al, 2001) which have been shown to modulate kainate-induced seizure activity in young animals, may modulate susceptibility in aged animals as well.…”
Section: Discussionmentioning
confidence: 99%
“…This decrease was associated with an increase in synaptic failures, indicating a presynaptic action possibly involving direct coupling between KARs and G proteins (Rodriguez-Moreno et al, 1997;Rodriguez-Moreno and Lerma, 1998;Lerma et al, 2001). An indirect mechanism of KA inhibition, involving an increase in action potential firing which produces enhanced GABA release, has also been postulated (Frerking et al, 1999).…”
Section: High Ka Concentrations Decrease Ipscsmentioning
confidence: 95%
“…In addition to being resistant to GYKI, KAR-mediated EPSCs have decay kinetics slower than their AMPA receptor mediated counterparts, and are inhibited by CNQX (For reviews, see (Chittajallu et al, 1999, Frerking and Nicoll, 2000, Lerma et al, 2001, Lerma, 2003, Lerma, 2006). Thus, we used these additional criteria to establish that the GYKI-resistant EPSCs in mEC neurons were indeed mediated by postsynaptic KARs.…”
Section: Postsynaptic Kars In Neurons Of the Superficial Mecmentioning
confidence: 99%
“…These receptors have been shown to both mediate and modulate synaptic transmission in both the central and peripheral nervous system (for reviews see (Chittajallu et al, 1999, Frerking and Nicoll, 2000, Lerma et al, 2001, Lerma, 2003, Lerma, 2006, Pinheiro and Mulle, 2006). Regarding the mediation of synaptic transmission, functional postsynaptic KARs have been demonstrated in a variety of cell types (Castillo et al, 1997, Vignes and Collingridge, 1997, Cossart et al, 1998, Frerking et al, 1998, DeVries and Schwartz, 1999, Kidd and Isaac, 1999, Li et al, 1999, Bureau et al, 2000, Cossart et al, 2002, Ali, 2003, Eder et al, 2003, Vitten et al, 2004, Wu et al, 2005, Jin et al, 2006 and may impose unique integrative properties to neurons (Frerking and Ohliger-Frerking, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation